2001
DOI: 10.1073/pnas.141221498
|View full text |Cite
|
Sign up to set email alerts
|

Cysteinyl leukotriene receptor 1 is also a pyrimidinergic receptor and is expressed by human mast cells

Abstract: The cysteinyl leukotrienes (cys-LTs) LTC4, LTD4, and LTE4 are a class of peptide-conjugated lipids formed from arachidonic acid and released during activation of mast cells (MCs). We now report that human cord-blood-derived MCs (hMCs) express the CysLT1 receptor, which responds not only to inflammation-derived cys-LTs, but also to a pyrimidinergic ligand, UDP. hMCs express both CysLT1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
165
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(173 citation statements)
references
References 31 publications
5
165
0
3
Order By: Relevance
“…A relationship between UDP and the CysLT 1 receptor has already been suggested, with the hypothesis that UDP may act directly on the receptor [42,43].…”
Section: Discussionmentioning
confidence: 97%
“…A relationship between UDP and the CysLT 1 receptor has already been suggested, with the hypothesis that UDP may act directly on the receptor [42,43].…”
Section: Discussionmentioning
confidence: 97%
“…Utilizing Cys-LT receptors, these mediators exert a diverse range of inflammatory effects including bronchoconstriction, smooth muscle proliferation, airway remodelling, fibrosis, and effector cell recruitment and activation [155]. Two known Cys-LT receptors, CysLT1 and CysLT2, have been characterized on a number of inflammatory cells, including mast cells [156,157]. 5-LO inhibitors and CysLT1 receptor antagonists are Histamine released by activated mast cells induces vasodilation, vascular permeability, and smooth muscle contraction in tissues via histamine receptors.…”
Section: Extracellular Targetsmentioning
confidence: 99%
“…To date, pharmacological studies identified two receptors for cys-LTs, named CysLT1 and CysLT2, whose characteristics were then largely confirmed by molecular biology studies that allowed the cloning of two genes for the human CysLT1 and CysLT2 receptors [5].…”
Section: Introductionmentioning
confidence: 95%